2022
DOI: 10.1039/d2tc03568e
|View full text |Cite
|
Sign up to set email alerts
|

Recyclability of CsPbBr3 quantum dot glass nanocomposites for their long-standing use in white LEDs

Abstract: The embedding of CsPbBr3 perovskite quantum dots (PQDs) in an inorganic glass matrix not only protects them against chemical, thermal, and photodegradation but also provides an effective strategy to isolate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Naji et al used periodic melt quenching and heattreatment processes to confirm its recyclable emission properties and fabricated a white LED to prove the structural and optical integrity of these composites. [177] WLED constructed from a blue LED chip, CsPbBr 3 NCs@glass composite, and a commercial red phosphor showed an aLE of 68.3 lm W −1 at a driving current of 20 mA. Lin et al reported the use of PeNCs@glass composite for backlight displays, reaching high PLQE for CsPbBr 1.5 I 1.5 NCs@glass (≈80%) and almost 100% for CsPbBr 3 NCs@glass composites.…”
Section: Leds and Displaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Naji et al used periodic melt quenching and heattreatment processes to confirm its recyclable emission properties and fabricated a white LED to prove the structural and optical integrity of these composites. [177] WLED constructed from a blue LED chip, CsPbBr 3 NCs@glass composite, and a commercial red phosphor showed an aLE of 68.3 lm W −1 at a driving current of 20 mA. Lin et al reported the use of PeNCs@glass composite for backlight displays, reaching high PLQE for CsPbBr 1.5 I 1.5 NCs@glass (≈80%) and almost 100% for CsPbBr 3 NCs@glass composites.…”
Section: Leds and Displaysmentioning
confidence: 99%
“…used periodic melt quenching and heat‐treatment processes to confirm its recyclable emission properties and fabricated a white LED to prove the structural and optical integrity of these composites. [ 177 ] WLED constructed from a blue LED chip, CsPbBr 3 NCs@glass composite, and a commercial red phosphor showed an aLE of 68.3 lm W −1 at a driving current of 20 mA.…”
Section: Applications Of Cspbx3 Ncs@glass Compositesmentioning
confidence: 99%
“…Several studies reported a combo of ultraviolet or blue light chips and QD glass as the new-generation light-emitting devices for illumination and displays. However, luminescence devices with near-ultraviolet or blue light-emitting semiconductor LED chips suffer a “sudden decline in efficiency” under the overcurrent situation, unrelated to the poor heat dissipation of the light-emitting diode (LED) chip. Consequently, it is extremely difficult to meet the demand for high-intensity lighting.…”
Section: Introductionmentioning
confidence: 99%